Applying WEFE nexus approaches for synergistically advancing the implementation of national biodiversity and climate commitments under the UNCBD and UNFCCC - Mabhaudhi, Tafadzwanashe; Elias, Marlene (2024)
Water, Energy, Food and Ecosystem (WEFE) nexus approaches can catalyse the synergistic realisation of National Biodiversity Strategies and Action Plans (NBSAPs) under the UN Convention on Biological Diversity (UNCBD) and Nationally Determined Contributions (NDCs) under the UN Framework Convention on Climate Change (UNFCCC). WEFE nexus thinking can inform and optimise projects and interventions that support both NBSAPs and NDCs, and mitigate duplication of efforts and inefficient use of limited funds. This brief outlines the ways in which nexus thinking can support achievement of national biodiversity and climate commitments under the UNCBD and UNFCCC, including through ecosystem-based adaptation (EbA) and nature-based solutions (NbS).